Cardiac surgery: the infinite quest. Part III - pediatric cardiac surgery: a discipline on its own - Neirotti,Rodolfo A. (2013)
ULTRAMINI-ABSTRACT: Although there are common grounds with adult cardiac surgery, it is important to understand the differences in the business plan, paths, manpower, mindset, training, and infrastructure that are essential in those institutions where pediatric cardiac surgery can and should be performed. Time to start thinking, it is not what we can do, but should we do it?